Russia Economic Report, No. 31, March 2014 : Confidence Crisis Exposes Economic Weakness - World Bank (Moscow, 2014)
Real Gross Domestic Product or GDP growth slowed to an estimated 1.3 percent in 2013 from 3.4 percent of 2012. In January 2013, we projected 3.6 percent growth for 2013, but while the global economy has continued to improve at a moderate pace, Russia's is struggling to find its footing. The first part of this report explores the recent economic developments that underlie this slowdown. To emerge from the downturn with improved long-term prospects Russia will need a combination of cyclical and structural policy measures. As the relative weight of the reasons for Russia's downturn is tilted toward structural factors, structural measures will need to lead the rebound. The lack of more comprehensive structural reforms in the past has led to a gradual erosion of investor confidence. This was masked by a growth model based on large investment projects, continued increases in public wages, and transfers, all fueled by sizeable oil revenues. Recent events around the Crimea have compounded the lingering confidence problem into a crisis of confidence and more clearly exposed the economic weakness of this growth model. Investor pessimism became the decisive factor affecting Russia's economic outlook, presented in part two of the report. The special focus note in part three discusses the link between Russia's growth in the past decade and how it fueled an unprecedented growth in household welfare.